Information System Planning Integrated database of training in food and nutrition at SEAMEO RECFON Using Togaf Architecture - Dodi Suswandi; Ivan Hanfi; Muhammad Yusro (Kirana Publisher (KNPub), 2023)
Southeast Asian Ministers of Education Organization Regional Center for Food and Nutrition (SEAMEO RECFON), is an organization of Southeast Asian ministers of education that focuses on food and nutrition. Currently, the application of SI / IT in the SEAMEO RECFON environment is not optimal, referring to the data base system that has not been integrated so that data and information exchange is not effective, the SI / IT investment made has also not given a good return, the training program in the field of food and nutrition each year is consistently not optimal, and several performance indicators are found not to meet their targets. Therefore, enterprise architecture planning is needed at SEAMEO RECFON which aims to formulate the principles and fundamentals of SEAMEO RECFON in accordance with the direction of its goals so as to produce healthy business processes, systems that can support training activities in the fields of food and nutrition, operations and infrastructure that can support the system to run well. This enterprise architecture planning is made using TOGAF (The Open Group of Architecture Framework) version 9.2 with the ADM (Architecture Development Method) method. This enterprise architecture planning produces a map of the main activities and support for food and nutrition training at SEAMEO RECFON, stakeholders, their focus, business objectives and basic principles, blueprints for business architecture targets, information systems architecture, technology architecture, and application implementation roadmap.